Sulfasalazine reduces bile acid induced apoptosis in human hepatoma cells and perfused rat livers. Issue 5 (1st December 2005) - Rust, C; Bauchmuller, K; Bernt, C; Vennegeerts, T; Fickert, P; Fuchsbichler, A; Beuers, U
Abstract : Background: Bile acid induced apoptosis in hepatocytes can be antagonised by nuclear factor κB (NFκB) dependent survival pathways. Sulfasalazine modulates NFκB in different cell types. We aimed to determine the effects of sulfasalazine and its metabolites sulfapyridine and 5-aminosalicylic acid (5-ASA) on bile acid induced apoptosis in hepatocytes. Methods: Apoptosis was determined by caspase assays and immunoblotting, NFκB activation by electrophoretic mobility shift assay and reporter gene assays, generation of reactive oxygen species (ROS) fluorometrically, bile secretion gravimetrically, and bile acid uptake radiochemically and by gas chromatography in HepG2-Ntcp cells and isolated perfused rat livers. Results: Glycochenodeoxycholic acid (GCDCA 75 µmol/l) induced apoptosis was reduced by sulfasalazine dose dependently (1–1000 µmol/l) in HepG2-Ntcp cells whereas its metabolites 5-ASA and sulfapyridine had no effect. Sulfasalazine significantly reduced GCDCA induced activation of caspases 9 and 3. In addition, sulfasalazine activated NFκB and decreased GCDCA induced generation of ROS. Bile acid uptake was competitively inhibited by sulfasalazine. In perfused rat livers, GCDCA (25 µmol/l) induced liver injury and extensive hepatocyte apoptosis were significantly reduced by simultaneous administration of 100 µmol/l sulfasalazine: lactate dehydrogenase and glutamate-pyruvate transaminase activities were reduced by 82% and 87%, respectively, and apoptotic hepatocytes were observed only occasionally. GCDCA uptake was reduced by 45 (5)% when sulfasalazine was coadministered. However, when 50% of GCDCA (12.5 µmol/l) was administered alone, marked hepatocyte apoptosis and liver injury were again observed, questioning the impact of reduced GCDCA uptake for the antiapoptotic effect of sulfasalazine. Conclusion: Sulfasalazine is a potent inhibitor of GCDCA induced hepatocyte apoptosis in vitro and in the intact liver.